Aeromagnetic delineation of iron ore deposits in a complex geological terrain aided by fuzzy logic - Fahad Abubakar; Felix Bamidele Fatoye; Momohjimoh Abdulsalami; Abdullateef Aliyu (Geosystems and Geoenvironment)
The discovery of iron ore deposits is crucial for Nigeria’s economic diversification. However, the Nigerian Bida Basin’s complex geology, extensive overburden, disputed stratigraphic boundaries and limited surface exposure hinder traditional geological and geophysical exploration methods. This study employs high-resolution aeromagnetic data covering 20,984.48 m² to delineate subsurface geological features and identify potential mineralized zones. Known ore deposits were used for validation. Signal enhancement filters, including the analytic signal (ANS), total horizontal derivative (THD), and Euler deconvolution, were applied to aid data interpretation. Depth estimates for mineralization sources range from 83.06 to 248.53 m (ANS) and 129 to 600 m (Euler). The THD highlights magnetic edge sources, with gradient amplitudes of 0.00008–0.00046 nT/m, covering 4621.42 m² (22%). The ANS refines the geometric configuration of these zones, identifying high-amplitude regions (0.07–0.16 nT/m) across 2989.34 m² (14%). These results strongly align with existing mining sites. Fuzzy membership and fuzzy overlay spatial analysis integrated the geophysical results, identifying 2667.39 m² (12.7%) as highly suitable for future metallic ore exploration. Validation using four known iron ore mining sites confirmed model accuracy, with all sites located within predicted high-potential zones. The predicted high mineralization potential zones are focus areas for further exploration and development. While the findings demonstrate the effectiveness of integrated geophysical enhancements in complex terrains, future exploration should incorporate ground-truth validation and economic feasibility assessments to refine exploration accuracy and ensure resource viability.